THE VALUE OF QIYAS IN ISLAMIC JURISPRUDENCE - Faisal Ahmadi; Muhammad Randhy Martadinata (STAI Ma'arif Jambi, 2020)
It is believed that Al-Qur’Én and Hadith are primary sources of Islamic law in determining law but Al-Qur’Én and Hadith are not codified as law. So, in determining law sometimes needs exegesis and certain method in determining law especially in new issue (furu’) that is not mentioned in Al-Qur’Én and Hadith. Qiyas is one of methodologies in determining or finding a new law besides both main sources of Islamic law. This article uses qualitative descriptive analysis. Researcher found that Majority of Ulama Scholars agree that Qiyas is one of some sources of Islamic law besides Al-Qur’Én, Hadith and Ijma’ (consensus).